Controlled Temperature Condition to Optimize the Storage Period and the Seeds Quality of Five Coffee Varieties - Wibowo, Ari; Akbar, Miftahur Rizqi; Wiradinata, Rizky (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
There is increasing interest of Indonesian coffee farmers to propagate coffee plants by using generative seeds due to easiness on distribution and production.The harvest time of coffee seed and the time for sowing/planting is separated by six months. This requires coffee seeds to be stored at least for the period.Technology for coffee storage is challenging due to the characteristic of coffee seeds as intermediate seeds which are sensitive to drying. The development of efficient and effective storage methods for coffee seeds is urgently needed. This study was aimed to evaluate the germination viability and quality of coffee seedlings obtained from the seeds that have been stored for up to 12 months in the warehouse. This study employed five coffee varieties including three Arabica coffee (USDA 762, P 88, and Gayo 1), and two Robusta coffee (propellegitim and Hibiro). One kilogram package of each variety (four replications) was stored in the warehouse at a temperature of 20 °C ± 2 °C. Each replication of the coffee seeds was then evaluated for germination viability and seedling quality on 0, 3, 6, 9, and 12 months of storage. Fresh coffee seeds (without storage) were used for comparison. The results showed a decrease in seeds’ moisture content during storage. Arabica coffee seeds were able to maintain their viability after six months of storage and Robusta coffee seeds after three months. Fresh coffee seeds showed the best seedling growth performance and seedling quality index. Arabica coffee USDA 762 stored for six months was able to produce seedlings with high plant performance, root length, stem diameter, and number of leaves similar to that of seedlings generated from fresh seed. Robusta coffee seedlings sown from fresh seeds had better quality compared to those from stored ones.